Dynamic Simulation of the Supply and Demand of Ecosystem Windbreak and Sand Fixation Service in the Wuding River Basin - Xuanchen Xiong; Zixiang Zhou; Xiaofeng Wang; Jing Li (Land)
Wind erosion can cause land degradation and other harmful effects. Examining the ecosystem windbreak and sand fixation service (WSFS) from the perspectives of supply and demand plays a crucial role in the continuous regulation of regional wind erosion. Through the enhancement of the revised wind erosion equation (RWEQ) model, integrated with uncertainty analysis, scenario simulation, and environmental factors calculation, the dynamic simulation of the supply of ecosystem windbreak and sand fixation service (WSFSS) and the demand of ecosystem windbreak and sand fixation service (WSFSD) in the Wuding River Basin in China was achieved, and specifically, a simulation framework for WSFSD and WSFSS was constructed. The results show that: (1) the uncertainty analysis can calculate the upper and lower limits of the range of parameter x (downwind distance) in the RWEQ model, and changes in the parameter x can make the simulation results of WSFSS and WSFSD more reasonable; (2) In the past 20 years, the WSFSS has shown a spatial distribution pattern of high in the northwest and low in the southeast. In terms of time, the annual WSFSS has shown a fluctuating growth trend with a growth rate of 8.06 t/a. The monthly WSFSS has shown a rising-fluctuating-declining trend; (3) The rationality of WSFSD was indirectly verified through the setting of scenario simulation. In terms of time, across the 252 months under study (January 2000–December 2020), 85% of the months witnessed WSFSD within the range of 1.0–1.4 kg/m2 in the Wuding River Basin. At the same time, the WSFSD also presented seasonal variation patterns. The WSFSD was relatively high in spring (March–May) and relatively low in summer (July–September) each year.